Evaluasi Kinerja Dan Jumlah Armada Angkutan Umum Pada Terminal Ubung Denpasar Utara Studi Kasus Trayek Terminal Ubung – Matahari Terbit - Hidayat, Dwi Wahyu; Oktopianto, Yogi; Ahmad, Rahmat; Yoga Anindita, Reza (Jurnal Keselamatan Transportasi Jalan (Indonesian Journal of Road Safety), 2022)
This Bus Rapid Transit (BRT) transportation is one of the supports for the mobilization of the Balinese people, especially in the SARBAGITA area (Denpasar, Badung, Gianyar and Tabanan). The purpose of this study was to determine the performance of inter-city transportation services within the province on the Trans Metro Dewata Bus located at the Ubung Terminal. This study was conducted using some primary data and secondary data that had been obtained from the field. The indicators for the performance of each mode are expressed in terms of Load Factor, Speed, Frequency and Headway. The results of the evaluation on the Trans Metro Dewata Bus public transportation show that the average Load Factor for the Ubung – Sunrise Terminal route is still below the standard. The average frequency also does not meet the standards, while the Headway exceeds the ideal Headway value of 10-15 minutes, the average frequency of the Ubung - Sunrise Terminal route does not meet the standards of 4-6 vehicles, the travel speed for transport routes In general, the Trans Metro Dewata bus does not meet the speed requirements, namely ≤ 20 km/hour.